Application of Human Resources Accounting in the International World (Period 2019 to 2022) - Radiyah, Fitra Tur; Maisyarah, Renny; Purba, Rahima Br (PT FORMOSA CENDEKIA GLOBAL, 2024)
Qualitative research does not test hypotheses; rather, the goal is to describe current phenomena or historical conditions or to gain a deeper understanding of variables. Secondary data is the type of data used in this research. To conduct this research, the author first collected and analyzed data from various sources, including literature reviews, journals, textbooks, the internet, and other relevant sources. The qualitative descriptive method, which involves collecting, organizing, and summarizing data to produce a clear picture of how human resource accounting is applied internationally, is the analytical technique used by the author in this research.